Analysis of Transit Oriented Development (TOD) Principles to Support Sustainable Transportation in Urban Areas - Darmawan, Rahman; Prasetyo, Widodo Adip; Irawan, Ari; Hariani, Mira Lestira (Riviera Publishing, 2024)
Implementing Transit Oriented Development (TOD) areas is an effort to overcome problems in urban areas due to rapid growth over time. These problems cause difficulties in mobility and land use, followed by traffic congestion, increased pollution, and accessibility that is not maximized. Therefore, the implementation of TOD is needed to support more sustainable movement in urban areas, especially in cities that have the potential to implement TOD. This study aims to discover the principles of TOD in a metropolitan area and the development strategies and recommendations that can be made to turn a metropolitan area into a TOD area. The method used in this research is the scoring method based on the TOD principles of ITDP standard 2017 and field observation activities. SWOT analysis was then conducted to determine the development strategy and recommendations that can be made. The research results at the study location still need to be included in the TOD area, where the study only scored 52 points. Efforts that can be made include adding recommendations for walking and cycling infrastructure at the study location so that it scores 66 points, which is included in the bronze category as a TOD area.